Enhanced perforin expression associated with dasatinib therapy in natural killer cells. (May 2018) - Iriyama, Noriyoshi; Takahashi, Hiromichi; Miura, Katsuhiro; Uchino, Yoshihito; Nakagawa, Masaru; Hatta, Yoshihiro; Takei, Masami
Highlights: Perforin expression in NK cells was higher in dasatinib-treated patients than in patients treated with imatinib or nilotinib. pSTAT1 and pSTAT3 levels were associated with the degree of perforin expression in NK cells. Th1 cytokines might influence dasatinib-induced immune response. Abstract: We investigated the effects of dasatinib on natural killer (NK) cell-induced signaling protein and perforin expression as well as plasma cytokine levels by analyzing blood samples from patients with well-controlled chronic myeloid leukemia receiving tyrosine kinase inhibitor (TKI) therapy. Perforin expression and phosphorylation of signal transducer and activator of transcription (STAT) 1, STAT3, Janus kinase (JAK) 1, and JAK2 in NK cells were evaluated by flow cytometry, and the levels of plasma cytokines, including interferon (IFN)-γ and interleukin (IL)-2, were determined by enzyme-linked immunosorbent assays in 40 patients (dasatinib, n = 23; imatinib, n = 11; and nilotinib, n = 6). Perforin levels in NK cells were higher in dasatinib-treated patients before TKI treatment; phospho (p)-STAT1 levels were closely correlated with pJAK1 and perforin levels, and pSTAT3 levels were correlated with pJAK2 and perforin levels. The correlation between pJAK1 and pSTAT1 was apparent in dasatinib-treated patients but not in other TKI-treated patients, and the correlation between pJAK2 and pSTAT3 was apparent in patients treated with other TKIs. Constitutive expression of IFN-γ was higher in patients treated with dasatinib or with other TKIs than in those who were in treatment-free remission (TFR). In contrast, constitutive expression of IL-2 was lower in patients treated with other TKIs than in those treated with dasatinib or in those who were in TFR. These results provided insights into the effects of dasatinib on JAK/STAT signaling in NK cells in vivo and the mechanisms underlying NK cell activation induced by dasatinib therapy.